2018
DOI: 10.1111/jpn.12995
|View full text |Cite
|
Sign up to set email alerts
|

Thymol in the intestinal tract of broiler chickens after sustained administration of thyme essential oil in feed

Abstract: Plant compounds occurring in phytogenic feed additives are involved in different pharmacological activities in the animal organism. Since the digestive tract acts as a first line of defence against foreign compounds, it is necessary to outline its response to dietary supplementation with bioactive plant components. Little information is available on the bioactivity of thymol as the main bioactive compound of Thymus vulgaris L. essential oil (TEO). The main objective of the present study was to provide a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…This variability may be due to the basal diet formulation, environment condition, the application dosage of the TVE, and the type of the selected bird (broiler, hen layer, quail, etc.). For example, performance parameters in broilers received 0.01%, 0.05%, 0.1% (w/w) thyme essential oils were not influenced significantly (Oceľová et al, 2018), while the quail fed on 1 g/kg of thyme oil showed greater BWG related to control (Khaksar et al, 2012). Similar to our results, the effects of 60, 100, and 200 mg/kg thymol and carvacrol combination were examined on broiler chicks and revealed that FI reduced linearly, while the birds received 200 mg/kg of this combination received the greatest BWG and feed efficiency (Hashemipour et al, 2013b).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This variability may be due to the basal diet formulation, environment condition, the application dosage of the TVE, and the type of the selected bird (broiler, hen layer, quail, etc.). For example, performance parameters in broilers received 0.01%, 0.05%, 0.1% (w/w) thyme essential oils were not influenced significantly (Oceľová et al, 2018), while the quail fed on 1 g/kg of thyme oil showed greater BWG related to control (Khaksar et al, 2012). Similar to our results, the effects of 60, 100, and 200 mg/kg thymol and carvacrol combination were examined on broiler chicks and revealed that FI reduced linearly, while the birds received 200 mg/kg of this combination received the greatest BWG and feed efficiency (Hashemipour et al, 2013b).…”
Section: Discussionmentioning
confidence: 89%
“…The effects of thyme and its active compound thymol on poultry performance parameters have been reported in current research publications and variable results observed (Hoffman-Pennesi and Wu, 2010;Khaksar et al, 2012;Mehdipour et al, 2014;Oceľová et al, 2018). This variability may be due to the basal diet formulation, environment condition, the application dosage of the TVE, and the type of the selected bird (broiler, hen layer, quail, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Another molecule can be transported through the basolateral membrane of enterocytes directly to the blood circulation. All these processes play a crucial role in affecting the thymol concentration in blood [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mode of action of herbs and plant extracts and the details about the accumulation of phenolic substances in animal tissues are not known or not completely understood [ 7 , 8 ]. In general, the bioavailability of dietary compounds depends on their digestive stability and the efficiency of their transepithelial passage [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation